Entering the Picture : Judy Chicago, the Fresno Feminist Art Program, and the Collective Visions of Women Artists. - Fields, Jill (New directions in American history., 2011)
In 1970, Judy Chicago and fifteen students founded the groundbreaking Feminist Art Program (FAP) at Fresno State. Drawing upon the consciousness-raising techniques of the women's liberation movement, they created shocking new art forms depicting female experiences. Collaborative work and performance art -- including the famous ""Cunt Cheerleaders""--Were program hallmarks. Moving to Los Angeles, the FAP produced the first major feminist art installation, Womanhouse (1972). Augmented by thirty-seven illustrations and color plates, this interdisciplinary collection of essays by artists and sch.